Evaluating the Impact of Brand Extension Attributes of Luxury Vehicle Brands in the CEE Region - Běloch, Marek; Machek, Martin; Olšanová, Květa; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
This thesis aims to elaborate on the current limits of literature on the topic of luxury attributes, specifically in relation to luxury vehicle brands and their brand extensions. The literature explains that luxury brand extensions often leverage prestige and heritage, as well as other rules iconic to the luxury segment, to expand into new product categories, offering consumers a cohesive experience by appealing to their personalities and lifestyles. The focus of the empirical research rests on quantitative respondent attitude and evaluation of specifically highlighted attributes iconic to luxury brands and their impact when confronted with downscale and horizontal luxury vehicle brand extensions. A study of 121 respondents was conducted, and its results were interpreted through descriptive, correlation, and dependency statistics. The findings indicate that the majority of attributes (Conspicuousness, Uniqueness, Hedonism & Extended-Self) do not translate along the different brand extensions. However, Quality and Sustainability show significant importance in their influence on extension attitudes. This provides insights for luxury vehicle product and marketing managers for actionable strategies along product and extension lines as well as marketing communication approaches.
Vedoucí práce: Martin Machek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses